A guide to the composition and functions of the extracellular matrix - Karamanos, Nikos K.; Theocharis, Achilleas D.; Piperigkou, Zoi; Manou, Dimitra; Passi, Alberto; Skandalis, Spyros S.; Vynios, Demitrios H.; Orian‐Rousseau, Véronique; Ricard‐Blum, Sylvie; Schmelzer, Christian E.H.; Duca, Laurent; Durbeej, Madeleine; et al. (The FEBS journal, 2021)
Extracellular matrix (ECM) is a dynamic 3‐dimensional network of macromolecules that provides structural support for the cells and tissues. Accumulated knowledge clearly demonstrated over the last decade that ECM plays key regulatory roles since it orchestrates cell signaling, functions, properties and morphology. Extracellularly secreted as well as cell‐bound factors are among the major members of the ECM family. Proteins/glycoproteins, such as collagens, elastin, laminins and tenascins, proteoglycans and glycosaminoglycans, hyaluronan, and their cell receptors such as CD44 and integrins, responsible for cell adhesion, comprise a well‐organized functional network with significant roles in health and disease. On the other hand, enzymes such as matrix metalloproteinases and specific glycosidases including heparanase and hyaluronidases contribute to matrix remodeling and affect human health. Several cell processes and functions, among them cell proliferation and survival, migration, differentiation, autophagy, angiogenesis, and immunity regulation are affected by certain matrix components. Structural alterations have been also well associated with disease progression. This guide on the composition and functions of the ECM gives a broad overview of the matrisome, the major ECM macromolecules, and their interaction networks within the ECM and with the cell surface, summarizes their main structural features and their roles in tissue organization and cell functions, and emphasizes the importance of specific ECM constituents in disease development and progression as well as the advances in molecular targeting of ECM to design new therapeutic strategies. Extracellular matrices (ECMs) are well‐orchestrated 3D ultrastructures that supportively encompass cells. ECM macromolecules include collagens, proteoglycans/glycosaminoglycans, laminins, elastin, other proteins/glycoproteins, proteolytic, and glycolytic enzymes. Cell‐matrix interactions via cell surface receptors, such as integrins and CD44, mediate biochemical and biomechanical signals to adapt cellular functions. ECM remodeling is critical in health and disease. This guide condensates main ECM structural components and their ability to cross‐interact and regulate cellular behavior